If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 = 2(3x + -1) + -2(x + 3) + 7 Reorder the terms: -5 + 5x = 2(3x + -1) + -2(x + 3) + 7 Reorder the terms: -5 + 5x = 2(-1 + 3x) + -2(x + 3) + 7 -5 + 5x = (-1 * 2 + 3x * 2) + -2(x + 3) + 7 -5 + 5x = (-2 + 6x) + -2(x + 3) + 7 Reorder the terms: -5 + 5x = -2 + 6x + -2(3 + x) + 7 -5 + 5x = -2 + 6x + (3 * -2 + x * -2) + 7 -5 + 5x = -2 + 6x + (-6 + -2x) + 7 Reorder the terms: -5 + 5x = -2 + -6 + 7 + 6x + -2x Combine like terms: -2 + -6 = -8 -5 + 5x = -8 + 7 + 6x + -2x Combine like terms: -8 + 7 = -1 -5 + 5x = -1 + 6x + -2x Combine like terms: 6x + -2x = 4x -5 + 5x = -1 + 4x Solving -5 + 5x = -1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 5x + -4x = -1 + 4x + -4x Combine like terms: 5x + -4x = 1x -5 + 1x = -1 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 1x = -1 + 0 -5 + 1x = -1 Add '5' to each side of the equation. -5 + 5 + 1x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = -1 + 5 1x = -1 + 5 Combine like terms: -1 + 5 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| 9-4x=15-12x | | 18=4 | | 4+7x=6x-7 | | 5t+7=20 | | 70-5x=3x+18 | | 7x^2+x-3=0 | | 9-8x=55-22x | | 4x^2+61x+180=0 | | -15-11y=-9-3y | | 3(x+4)=2(2x-5)+13 | | 8x-1=11+4x | | 5(2x+7)=25 | | 6-7x=46-14x | | 15x^2-28+5=0 | | h^2+10h=-21 | | 5(x-6)+6=7(x+2)-6 | | 3x+8=-62-7x | | 5x+10=11-4x | | 6.4=x+3.7 | | 2x^2+13x+33=12 | | -16t+t+0=0 | | 4x-16=2x+2 | | -4t^2+t+0=0 | | -[9z-(15z+3)]=3+(5z+4) | | 0.5x-4+2x=5 | | b^2-7b-18=0 | | 2[k-(4k+13)+3]=2(k+10) | | 2x-4+2x=5 | | (x-8)-11=-10 | | 0.8p=32 | | x^2-4+2x=5 | | 5x-4=3x+12 |